The level of empathy among students of the first three grades in the point of view of their teachers in schools in the schools affiliated to the Marka Brigade in Jordan in the light of some variables - Al- Rbehat, Eman Majed (Journal of Educational and Psychological Sciences, 2021)
This study aimed at investigating the level of empathy among students of the first three grades in the teacher’s point of view in the schools affiliated to the Marka Brigade in Jordan in the light of these variables: Gender, Qualifications and the teacher’s years of experience. And the sample was formed which was selected randomly between (293) teachers during the second semester of the year (2020/2021), and to achieve the goals of the study a scale was developed to measure the level of empathy, and after verifying the validity and reliability of the scale it was applied to the study sample members, and to find out the level of empathy among students in the first three grades the arithmetic means and standard deviations of the scores of the study sample members were calculated on the study tool, and to examine the differences attributed to the teacher’s qualification and experience, the one- way analysis was used. and the study results indicated that the average response of the members of the sample was high, and the study results also indicated that there are no statistically significant differences in the empathy level among the students of the first three grades according to the gender variable of the teacher, and that there are no statistically significant differences at the level of significance (α≤0.05) at the total level of empathy among students according to the qualification variable of the teacher, and that there are no statistically significant differences at the level of significance (α≤0.05) at the total level of empathy among students of the first three grades according to the experience variable of the teacher. and the researcher concluded a set of recommendations, most notably designing training programs for teachers responsible for the first three grades and activating their role in developing the emotional and social skills of their students, and studying empathy among students at other age stages and from their point of view.
Keywords: Empathy; First three grades; Teacher’s point of view; Marka Brigade; Jordan